2003
DOI: 10.1186/1471-2458-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Is drinking water a risk factor for endemic cryptosporidiosis? A case-control study in the immunocompetent general population of the San Francisco Bay Area

Abstract: Background: Cryptosporidiosis, caused by Cryptosporidium, is an enteric illness that has received much attention as an infection of immunocompromised persons as well as in community outbreaks (frequently waterborne). There are, however, no studies of the risk factors for sporadic community-acquired cryptosporidiosis in the immunocompetent US population. We undertook a case-control study in the San Francisco Bay Area as part of a national study sponsored by the Centers for Disease Control and Prevention to asce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…A similar study conducted among immunocompetent persons in the same geographic region found that cryptosporidiosis was only associated with foreign travel but not tap water consumption [34]. This discordance in results supports the observation that host susceptibility, i.e., immune status, is the primary determinant of developing cryptosporidiosis among AIDS patients.…”
Section: Discussionsupporting
confidence: 68%
“…A similar study conducted among immunocompetent persons in the same geographic region found that cryptosporidiosis was only associated with foreign travel but not tap water consumption [34]. This discordance in results supports the observation that host susceptibility, i.e., immune status, is the primary determinant of developing cryptosporidiosis among AIDS patients.…”
Section: Discussionsupporting
confidence: 68%
“…These foods might have conferred a direct protective nutrient effect, been markers for more favorable general nutrition, or contained small numbers of oocysts derived from water used for irrigation and preparation sufficient to induce immune boosting ( 3 , 30 , 31 ). A recent study of sporadic cryptosporidiosis in the San Francisco Bay Area also failed to show an association with tap water, but the study was small ( 32 ). …”
mentioning
confidence: 95%
“…The contamination rate of Rotavirus was reported 55.6% among children of northwest of Iran, reported by Ghorashi et al (17). Because of the same dissemination pattern of Cryptosporidium and Giardia through oral-fecal pathway, it seems that contaminated drinking water in urban regions and its exposure to contaminated animals in rural regions may contribute in the dissemination of organisms (18). Sayyari et al (19) reported the frequency of G. lamblia and E. histolytica among Iranian people 10.9% and 1.0%, respectively.…”
Section: Discussionmentioning
confidence: 88%